High Prevalence and Diversity Characteristics of blaNDM, mcr, and blaESBLs Harboring Multidrug-Resistant Escherichia coli From Chicken, Pig, and Cattle in China - Liu, Zhihai; Wang, Ke; Zhang, Yaru; Xia, Lining; Zhao, Li; Guo, Changmei; Liu, Xudong; Qin, Liting; Hao, Zhihui (Frontiers in Cellular and Infection Microbiology, 2022)
The objective of study was to understand diversity characteristics of ESBL-producing Escherichia coli (ESBL-EC) in chicken, pig and cattle. A high prevalence of ESBL-EC (260/344) was observed in all animals with prevalence rates of 78.6% (110/140) for chicken, 70.7% (58/82) for cattle and 75.4% (92/122) for swine. However, the resistance rates presented significant differences in different animal origin ESBL-EC, where resistance to CTX, GEN, IMP, NEO and OFL were highest in chicken ESBL-EC, then cattle and lowest in swine. Seriously, most ESBL-EC harbor multidrug resistance to antibiotics (MDR, ≥3 categories antibiotics), and the MDR rates of ESBL-EC was highest in chicken (98.18%), followed by swine (93.48%) and lowest in cow (58.62%), while the same trend also was observed in MDR of ≥5 categories antibiotics. This high prevalence and resistance can be partly interpreted by high carriage rates of β-lactamases CTX-M (n=89), OXA (n=59), SHV (n=7) and TEM (n=259). A significant difference of the β-lactamase genes also presented in different animal ispecies solates, where chicken origin ESBL-EC possessed higher carriage rates of almost all genes tested than cattle and swine. Notably, 8 chicken origin ESBL-EC carried transferable plasmid-mediated blaNDM-1 or blaNDM-5, especially, of which 4 ESBL-EC also contained colistin resistance gene mcr-1 confirmed by genomic analysis. More interestingly, two deletions events with 500-bp deletion in ΔISAba125 and 180-bp in dsbC were observed in 3 blaNDM-5 IncX3 plasmids, which is the first discovery. This showed the instability and horizontal transfer of blaNDM genetic context, suggested blaNDM are evolving to “pack light” to facilitate rapid and stable horizontal transfer. STs and PFGE showed a diversity patterns. The most prevalent STs were ST48 (n=5), ST189 (n=5), ST206 (n=4), ST6396 (n=3), ST10 (n=3), and ST155 (n=3), where ST48 ESBL-EC originated from three food animal species. The STs of all blaNDM positive ESBL-EC were attributed to 3 ST types, including ST6396 (n=2), ST206 (n=2), and ST189 (n=4), where ST189 was also unique type for 4 mcr-1-carrying ESBL-EC. In conclusion, we suggest that the three animal species ESBL-EC show similar high prevalence, diversity in isolate lineages, and significant discrepancies in antibiotic resistance and resistance genes.